2012
DOI: 10.1038/ncomms1651
|View full text |Cite
|
Sign up to set email alerts
|

c-Src and IL-6 inhibit osteoblast differentiation and integrate IGFBP5 signalling

Abstract: Interleukin-6 (IL-6) and c-src impair osteoblast maturation in vitro and in vivo. Given the similar effects of these factors, they are likely to establish a functional loop to maintain osteoblasts in a less mature status. Here we describe a pathway whereby c-src stimulates IL-6 expression through the sTAT3 factor, which, in response to IL-6 induces insulin-like growth factor 5 (IGFBP5), a c-src activating factor that amplifies this loop only in immature osteoblasts. In contrast, in mature osteoblasts, IGFBP5 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(71 citation statements)
references
References 28 publications
1
69
0
1
Order By: Relevance
“…Interestingly, both CTGF and Igfbp5 have been independently found to inhibit osteoblast maturation and differentiation [63,64] while MGP is an ECM protein that has been shown to inhibit mineralization and apoptosis of chondrocytes [65]. These findings suggest that interactions between leukemia and the BM stroma induce changes towards an undifferentiated state of the tumor microenvironment that could contribute to disease progression and chemotherapy resistance [66].…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, both CTGF and Igfbp5 have been independently found to inhibit osteoblast maturation and differentiation [63,64] while MGP is an ECM protein that has been shown to inhibit mineralization and apoptosis of chondrocytes [65]. These findings suggest that interactions between leukemia and the BM stroma induce changes towards an undifferentiated state of the tumor microenvironment that could contribute to disease progression and chemotherapy resistance [66].…”
Section: Discussionmentioning
confidence: 94%
“…Recently, we demonstrated that in osteoblasts c-Src regulates interleukin (IL)-6 and insulin-like growth factor binding protein (IGFBP)-5 expression (Peruzzi et al, 2012). More in details, c-Src controls IL-6 expression acting on STAT3, which is a downstream component of the IL-6 pathway and a transcription factor for IL-6 itself.…”
Section: C-src Regulation Of Osteoblast Differentiationmentioning
confidence: 99%
“…On the other hand, in mature osteoblasts c-Src is barely expressed and therefore this loop is inactive, although IGFBP5 is still expressed under the control of Runx2. In this context, IGFBP5 has been observed to enhance osteoclast formation and bone resorption, thus unveiling its new role in the coupling between osteoblast and osteoclast activities (Peruzzi et al, 2012).…”
Section: C-src Regulation Of Osteoblast Differentiationmentioning
confidence: 99%
“…Alternatively, local coupling factors linking bone resorption to subsequent formation have long been proposed as the key regulator of the bone remodeling process. TGFβ and IGF-1 (7,15,16) were postulated to function as a coupling factor, but during the decade, more candidates were raised-complement component 3a (24), matrix IGF-1 (6), E-secletin ligand 1 (40), integrated actions of c-Src, IL-6 and IGFBP5 (28), semaphorin 3A (14), and Dlx5 (29). Among these molecules, we postulated that EphB4/ephrinB2 (41) would behave as coupling factors as reported previously (21).…”
Section: Immnolocalization Of Ephrinb2 and Ephb4 In C-fosmentioning
confidence: 99%